2020
DOI: 10.1111/jgs.16344
|View full text |Cite
|
Sign up to set email alerts
|

Time Spent Away from Home in the Year Following High‐Risk Cancer Surgery in Older Adults

Abstract: OBJECTIVES To understand where older adults spend time (at home, in the hospital, or in a nursing home) in the year following high‐risk cancer surgery. DESIGN Retrospective cohort study. SETTING Medicare beneficiaries using data from Medicare Inpatient claims to ascertain hospital days and the Minimum Data Set to ascertain nursing home days. PARTICIPANTS Beneficiaries who underwent high‐risk cancer surgery (cystectomy, pancreaticoduodenectomy, gastrectomy, or esophagectomy) were identified to determine cumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…For example, two recent publications studied the new patient-oriented outcome of time spent away from home following emergency general surgery and high-risk cancer surgery. 12,13 The authors of the current study demonstrated the utility of baseline frailty measures for predicting hospital-acquired geriatric syndromes. Hospital-acquired geriatric syndromes are detrimental to both traditional outcomes, such as mortality, and longer-term outcomes valued by older adults, such as maintaining independence (Figure 1).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…For example, two recent publications studied the new patient-oriented outcome of time spent away from home following emergency general surgery and high-risk cancer surgery. 12,13 The authors of the current study demonstrated the utility of baseline frailty measures for predicting hospital-acquired geriatric syndromes. Hospital-acquired geriatric syndromes are detrimental to both traditional outcomes, such as mortality, and longer-term outcomes valued by older adults, such as maintaining independence (Figure 1).…”
mentioning
confidence: 76%
“…In response to this practical need for more data about geriatric‐focused predictors and outcomes for older surgical patients, the current study and other recent studies have focused on important patient‐centered outcomes. For example, two recent publications studied the new patient‐oriented outcome of time spent away from home following emergency general surgery and high‐risk cancer surgery 12,13 …”
Section: Figurementioning
confidence: 99%
“…This kind of violence has the effect of establishing the legitimacy of a decision discourse, from an agent or institution (Manouchehri, Ghorbi, Hosseini, Nasiri & Karbakhsh, 2009). Elderly people are the group that is most intimidated by the harmful effects of social distancing, since they are at greater risk for Coronavirus contamination and register the most serious outcomes and death due to infection (Applegate & Ouslander, 2020;Suskind et al, 2020). The data reflect on the elderly's daily lives due to a high need of social distancing, although there is an initial resistance on the part of a minority to respect social distancing.…”
Section: Discussionmentioning
confidence: 99%
“… 27 For example, a study of Medicare beneficiaries undergoing four high risk cancer surgeries showed that there is substantial time away from home in the year following surgery. 28 To summarize, surgical goals for all patients should be frankly discussed and put in the context of life expectancy, overall prognosis and the possible loss of function.…”
Section: General Principlesmentioning
confidence: 99%